Intracellular Protective Functions and Therapeutical Potential of Trehalose - Dorota Kuczyńska-Wiśnik; Karolina Stojowska-Swędrzyńska; Ewa Laskowska (Molecules, 2024)
Trehalose is a naturally occurring, non-reducing saccharide widely distributed in nature. Over the years, research on trehalose has revealed that this initially thought simple storage molecule is a multifunctional and multitasking compound protecting cells against various stress factors. This review presents data on the role of trehalose in maintaining cellular homeostasis under stress conditions and in the virulence of bacteria and fungi. Numerous studies have demonstrated that trehalose acts in the cell as an osmoprotectant, chemical chaperone, free radical scavenger, carbon source, virulence factor, and metabolic regulator. The increasingly researched medical and therapeutic applications of trehalose are also discussed.